Overweight and obesity in older adults with an intellectual disability - Ryan, Judy Mary (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2024)
This research is situated within the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing (IDS-TILDA) a nationally representative study involving 753 participants with an intellectual disability (ID) over the age of 40 years. Ethical approval was granted by the University of Dublin, and service providers involved. Face-to-face interviews were conducted with topics ranging from demographics to behavioural health and social characteristics. A Computer Assisted Personal Interview (CAPI) system and Pre Interview Questionnaire (PIQ) formed part of data collection. The PIQ included health related questions and doctors diagnosed Chronic Health Conditions (CHC). Objective measures of weight, height and waist circumference were collated during a health fair. In Wave 3 of IDS-TILDA, a food frequency questionnaire (FFQ), framed on a Survey of Lifestyle Attitudes and Nutrition was completed by participants and included questions on food consumption across all food groups to determine consumption levels. Portion Per Day (PPD) were allocated to the shelfs of the food pyramid (greater than daily recommendations, recommendations per day and less than recommended per day) and categorised into shelf count based on PPD. Analyses was correlated with weight status against national recommendations based on the food pyramid. Pearson¿s chi-square test determined significant bivariate associations (p-value <0.05) between overweight/obesity, demographic characteristics and CHC and shelves on the food pyramid (95% confidence interval). Logistic regressions were assessed based on the p-value likelihood ratio test (0.05 level of significance) and Nagelkerke R2. Wald test p-values (0.05 level of significance). Odds ratios and associated 95% confidence intervals were included. Women (72.2%, n=239/331) and men (64.7%, n=156/241) were overweight/obese as were participants at midlife (aged between 50-64 years) (70.1%, n=204/291). Significant associations were identified between BMI (overweight/obese), level of ID and living arrangements (p<0.001). CHC were reported in overweight/obese participants. Gastrointestinal disorders (59.2%, n=148/250) (p<0.001); respiratory (89.2%, n=33/37) (p-0.006) and musculoskeletal disease (56.7%, n=80/141) were statistically significance (p<0.001). Women at menopause with overweight/obesity were aged between 50-64 years (65.8%, n=106/161). Significant association was found between CHC, menopause, level of ID (p value= <0.001); residents type (p value= <0.043); GIT conditions 36% (n=58/161) (p=0.001); neurological conditions 33.5% (n=54/161) (p=0.002) and muscular skeletal disorders (30.4%, n=49/161) (p=0.001). Women age between 50-64 years 65.9% (n=116/176) had a waist circumference risk exposure for metabolic disease risk (p=0.010). GIT disorder (p=0.007) and neurological conditions (p=0.013) were statistically significant. Considering dietary patterns, 45.4% (n=129/284) of overweight/obese participants consumed less fruit and vegetables than the recommended 5-7 PPD with 46.3% (n=74/160) of women consuming < RDA as did 44.4% (n=55/124) of men. In contrast, almost all overweight/obese women exceeded the RDA for high sugar, salt and fat foods (97.5%, n=155/159) as did 96% (n=119/124) of men. This study found overweight/obesity omnipresent among ID. Consequently the negative effects on the health and wellbeing of people with ID is prominent, particularly so for women at midlife.
APPROVED